Development of Natural Science E-Module on Motion Materials for Junior High School Students - Lazaro Kumala Dewi; Indri Astuti; Aloysius Mering (JETL (Journal of Education, Teaching and Learning), 2023)
The goals of this research are to produce an innovative, interactive, and practical Natural Science E-Module of Motion Materials, this learning can be more interesting, fun, and also the students can learn independently. This research using 4-D model (Four D-Models) with 4 steps they are define, design, develop, and disseminate/deploy. The subjects of this research were students of class VIII grade of SMP Negeri 1 Sungai Raya Pontianak and SMP Negeri 11 Pontianak. The data collecting of this research is using interview techniques, questionnaires, and tests. The assessment of E-Module by the experts obtained eligibility = 86,67% with "Excellent" qualification. The assessment of e-module by the design experts obtained = 79,17% with "Good" qualification. This e-module being assessment by media expert obtained = 82,5% with "Excellent" qualification. The student response which one to one class (individual) to the product obtained = 82,22% including the criteria "Very Interesting". Student response which small group class obtained = 90.07% including the criteria "Very Interesting". The effectiveness of the product is seen from the student's learning results using the effect size test. The effectiveness of Natural Science E-Module obtained = 1,748 which the criteria is "Large". This e-module using App Inventor which is very effective to the students to improve student’s learning outcomes.